2017
DOI: 10.4317/jced.53524
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography assessment of temporomandibular joint position and dimensions in patients with class II division 1 and division 2 malocclusions

Abstract: BackgroundThis study aimed to investigate and compare the positions and dimensions of the temporomandibular joint and its components, respectively, in patients with Class II division 1 and division 2 malocclusions.Material and MethodsComputed tomography images of 14 patients with Class II division 1 and 14 patients with Class II division 2 malocclusion were included with a mean age of 11.4 ± 1.2 years. The following temporomandibular joint measurements were made with OsiriX medical imaging software program. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…Anatomical changes can be seen in the parts with obvious reconstruction. Some scholars have examined the differences in the temporomandibular joint related to diverse malocclusions, and confirmed that the morphological structure and positional relationship between the condyle and articular fossa may be different in patients with various types of malocclusion [3,4].…”
Section: Introductionmentioning
confidence: 97%
“…Anatomical changes can be seen in the parts with obvious reconstruction. Some scholars have examined the differences in the temporomandibular joint related to diverse malocclusions, and confirmed that the morphological structure and positional relationship between the condyle and articular fossa may be different in patients with various types of malocclusion [3,4].…”
Section: Introductionmentioning
confidence: 97%
“…As different types of malocclusion have varying degrees of condyle displacement [ 21 , 22 ], we predicted that the long-term mandibular functional shift also led to condyle displacement and that the condyle finally relocated because of a neuromuscular adaption. Since the centric relation (CR) theory was put forth, most of the controversies were related to the position of the condyle in the glenoid fossa, which is clinically invisible [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) studies found that anterior joint space was significantly wider in class II malocclusion subjects, with a deeper mandibular fossa. 35,36 Another CT study showed a general significant pattern of a more convex and anteriorly positioned condyles. 37 Thus, temporomandibular joint (TMJ) anatomy seems to be distinct in patients with class II malocclusion, subjecting such delicate orofacial structure to a more damage tendency.…”
Section: Discussionmentioning
confidence: 99%